Pengaruh intervensi pemberian makanan tambahan (PMT) berbasis menu lokal terhadap wasting pada balita di Sukoharjo - Nur Lailatul Muhlishoh; Listiyani Hidayati; Muwakidah Muwakidah (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Supplementary feeding (PMT) is one of the interventions aimed at reducing the incidence of wasting among toddlers. The macronutrient content in PMT plays a role in improving toddlers' weight, thereby potentially reducing wasting rates. Objective: To determine the effect of PMT in reducing wasting rates among toddlers.Methods: This study used a pre-and-post design without a control group, involving 35 subjects selected through a multistage random sampling method. The intervention was conducted over 90 days from January to March 2024, using a 10-day menu cycle. Data on wasting toddlers were obtained from secondary data provided by the Sukoharjo District Health Office, measured using the Weight-for-Height (WHZ) indicator and analyzed using WHO Anthro. A wasting child is defined as having a WHZ score between -3 SD and <-2 SD, while severe wasting is defined as a WHZ score <-3 SD. Data analysis employed the Wilcoxon test for non-normally distributed data. Results: The study showed that the average WHZ score of toddlers before PMT was -2,4 SD, improving to -1,8 SD after the intervention. PMT increased the nutritional status of wasting and severely wasting toddlers to normal in 57,1% of cases. A significant difference was observed in the nutritional status of toddlers before and after PMT (P = 0,001).Conclusion: PMT is proven effective in reducing the prevalence of wasting among toddlers.